Endoscopic cerebrospinal fluid leak repair: how we do it - Patel, Kalpesh; Gugliani, Abhishek; Vishwakarma, Rajesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Cerebrospinal fluid (CSF) rhinorrhoea is characterized by a defect in the barriers which separate the subarachnoid space from sinonasal tract resulting in the leakage of watery fluid from the nose. Management of CSF rhinorrhoea is by both conservative and/or surgical approach. Transnasal endoscopic method has become the preferred surgical method for the repair of CSF leak because of less complication as compared to the open approach. To evaluate the results of patients who underwent endoscopic repair of CSF rhinorrhoea over a period of 5 years at BJ Medical College, Civil Hospital, Ahmedabad. Methods: 118 patients were included in this retrospective study who underwent CSF leak repair by nasal endoscopy over a period of 5 years between 2011-2016 in the department of ENT at BJ Medical College, Civil Hospital, Ahmedabad. As per review of the records, these patients were diagnosed with CSF leak on the basis of their history, clinical examination, and radiological investigations. Materials used for the repair were fat, fascia lata, fibrin sealant, and/or vascular flap. Results: Primary surgery was successful in 110 (93%) of cases. In 8 (7%) cases, there was a recurrence of leak which was managed by either conservative management (5 cases, 4%) or by re-exploration (3 cases, 3%). Conclusions: Transnasal endoscope is an important tool for the evaluation and subsequent treatment of CSF rhinorrhoea. Endoscopic repair of CSF rhinorrhoea is safe, effective, has a low complication rate and has almost completely replaced the open technique.